Increasing Pyruvate Concentration Enhances Conidial Thermotolerance in the Entomopathogenic Fungus Metarhizium robertsii - Wu, Congcong; Zhang, Xing; Fang, Weiguo (Frontiers in Microbiology, 2019)
The fungal entomopathogens Metarhizium spp. have been developed as environmentally friendly mycoinsecticides. However, heat stress severely reduces the viability of Metarhizium conidia in the field, which is an important obstacle to the successful use of these mycoinsecticides. Heat treatment induces rapid accumulation of pyruvate, which timely scavenges heat-induced ROS (reactive oxygen species) in hyphal cells of M. robertsii. However, in heat-treated conidia, pyruvate accumulation occurs later than the rapid production of ROSs, which could harm the conidial cells. In the present study, a transgenic M. robertsii strain was constructed with the pyruvate kinases gene overexpressed during conidiation. Two independent transformants of the transgenic strain produced conidia under optimal conditions with elevated pyruvate concentration. This inhibits the rapid heat-induced ROS production and prevents the collapse of mitochondrial membrane potential, thereby increasing conidial tolerance to heat stress. In conclusion, the tolerance of M. robertsii conidia to heat stress was improved by increasing the conidial pyruvate concentration, which could be translated into a more effective pest control.